RESULTS OF AN OBSERVATIONAL PROSPECTIVE STUDY OF THE EFFICACY AND SAFETY OF BELIMUMAB (BENLYSTA®) IN SYSTEMIC LUPUS ERYTHEMATOSUS IN REAL CLINICAL PRACTICE - E. A. Aseeva; S. K. Soloviev; A. A. Mesnyankina; T. M. Reshetnyak; N. E. Lopatina; S. I. Glukhova; E. L. Nasonov (Научно-практическая ревматология)
Therapy for systemic lupus erythematosus (SLE) remains challenging. The long-term use of glucocorticoids (GC) and cytostatics considerably improves life expectancy, but at the same time favors the development of irreversible organ damages. To evaluate the efficacy of belimumab (BLM), a biological agent, that blocks B-lymphocyte-stimulating factor registered for the treatment of active SLE, is an important task of the practice of rheumatology.Objective: to evaluate the efficacy and safety of BLM in patients with high and moderate SLE activity.Subjects and methods. The investigation enrolled 16 patients with a Systemic Lupus Erythematosus Disease Activity Index (SLEDAI-2K) score of 6 to 19, who were positive for antinuclear factor (100%) and had low complement levels and high anti-native DNA antibodies (81%). BLM was used as monthly intravenous infusions at a dose of 10 mg/kg. The efficiency and safety of the therapy were evaluated monthly and 1 year after the initiation of treatment with BLM; SLE activity was estimated using SLEDAI-2K; a physician’s global assessment of disease activity on a visual analogue scale (VAS); anti-DNA antibody level changes, complement levels, a GC dose, damage index, and adverse events were determined.Results and discussion. BLM therapy proved to be effective in 62% of cases at 1 year after therapy initiation. At 1 month, SLE activity significantly decreased with SLEDAI-2K score diminishment from 9.31±3.21 to 6.25±2.80 in the entire group (p < 0.04). Over a month, the physician’s global assessment of disease activity significantly reduced from 19.25±6.60 to 13.68±3.97 mm (р<0.01) and reached minimum (8.28±6.87 mm) by 10 months of therapy. There was a significant decrease in anti-DNA antibodies and an increase in complement C4 level at 5 and 3 months of therapy, respectively. Six of the 10 patients who had received a complete cycle of BLM therapy achieved remission at 12 months. The dose of GC was significantly reduced at 6 months of therapy. Adverse events were rare. BLM was discontinued because of its inadequate efficacy in 4 patients.Conclusion. Twelve-month therapy with BLM is effective in patients with high and moderate SLE activity according to SLEDAI-2K and with high immunological activity. The use of BLM in SLE contributes to a GC dose reduction and fails to cause serious adverse events.